Tsunami loads on coastal structures - Yao, Chia Hsiang (2012)
The main focus of this final year project is to study the effectiveness of the sand dunes in the dissipation of the tsunami wave energies. To simulate the leading wave of a tsunami, a solitary wave was generated over the various conditions such as different water depth and wave heights, and the climbing of a slope. The experiment was then carried out to study the reduction in wave heights and surface run-ups caused by the placement of sand dunes at various locations.